2021
DOI: 10.1088/1757-899x/1094/1/012170
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Buckling Investigation of Composite Materials to be used in the Prosthetic Pylon Manufacturing

Abstract: A prosthetic pylon is a part of an artificial lower limb, which is a very interesting area of biomedical engineering today. The research aims to show the hung innovations and developments of new suggested composite material, to modify the prosthetic pylon (which is generally made of lightweight metal such as aluminum, titanium, stainless steel, or an alloy of these), extends its life and increase the comfort of its user. Vacuum bagging technique was used to manufacture the samples which consist of constant per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…1. The modulus of elasticity, yield strain, and ultimate stress of the materials utilized to manufacture prosthetic limb sockets were calculated using a computer-numerical control machine (CNC) to cut for each sample according to the American Society of Testing Materials ASTM D638(I) dimensions [34,35]. The samples were tooled as shown in Fig.…”
Section: Instrumentsmentioning
confidence: 99%
“…1. The modulus of elasticity, yield strain, and ultimate stress of the materials utilized to manufacture prosthetic limb sockets were calculated using a computer-numerical control machine (CNC) to cut for each sample according to the American Society of Testing Materials ASTM D638(I) dimensions [34,35]. The samples were tooled as shown in Fig.…”
Section: Instrumentsmentioning
confidence: 99%
“…Finally, support the composite plate structure, as SSFF and CCFF plate supported, then input the mechanical properties of materials were calculated by experimental technique, [72][73][74][75][76], and then solve the considered case study to evaluate the composite plate's buckling behavior, with different nanomaterials effect. Then, compare the numerical results calculated with the experimental results, and the discrepancy between the results is evaluated [77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92].…”
Section: Numerical Analysismentioning
confidence: 99%
“…Samah F. H. et al worked to select the appropriate density of the material in accordance with the mechanical prosperities required by the 3D-printing application in which it will be employed in the manufacture of the prosthetic pylon [8]. The research of Hayder Zaher Abdalikhwa et al aims to show the hung improvements and developments of new suggested composite materials, to change the prosthetic pylon by boosting the user's comfort and extending the life of the prosthetic pylon [9]. Zainab H. Zaier and Kadhim K. Resan worked on manufacturing prosthetic shanks from porous functionally graded materials (ABS filament materials) by additive fabricating technique [10].…”
Section: Introductionmentioning
confidence: 99%